Clinical Characteristics and Outcomes of Acute Myeloid Leukemia Patients Harboring Triple Mutations and the Potential Prognostic Value of - Yujie Niu MD; Xingchun Luo MD; Xiaoxiao Yang MD; Yuancheng Guo MD; Xiao Tang MD; Long Zhao MD; Jinli Jian MD; Bei Liu MD, PhD (Cancer Control)
Introduction Nucleophosmin 1 ( NPM1 ), FMS-like tyrosine kinase 3-internal tandem duplication ( FLT3-ITD ), and de novo methyl transferase 3 A ( DNMT3A ) triple-mutated acute myeloid leukemia (AML) represents a distinct entity with poor outcomes. Methods We explored the gene mutation spectrum and clinical characteristics of 165 AML patients retrospectively, particularly comparing patients with NPM1/FLT3-ITD/DNMT3A triple-mutations and those without. Results Our results demonstrated significantly elevated white blood cell counts ( P < 0.001), bone marrow blast percentages ( P = 0.037), and platelet counts ( P = 0.007) in the triple-mutated cohort (6.7%) compared to the non-triple-mutated patients. Furthermore, all triple-mutated cases were classified as the M4/M5 subtype of the French-American-British classification ( P = 0.017). Although no significant difference in complete remission rates was observed between the groups after initial treatment, the median overall survival for triple-mutated AML patients was only 4 months. Using the Gene Expression Omnibus (GEO) database and bioinformatics, we compared AML NPM1 mut FLT3-ITD mut DNMT3A mut and AML NPM1 mut FLT3-ITD mut DNMT3A wt . A total of 246 AML patients from the GEO dataset were included to evaluate the expression profiles of differentially expressed genes. The guanine nucleotide-binding protein subunit γ 4 ( GNG4 ) was differentially expressed between AML NPM1 mut FLT3-ITD mut DNMT3A mut and AML NPM1 mut FLT3-ITD mut DNMT3A wt , which had the most adjacent nodes among hub genes. The prognostic value of GNG4 was further validated in AML patient samples through qRT-PCR. Conclusion Clinical validation indicated a substantial downregulation of GNG4 in AML NPM1 mut FLT3-ITD mut DNMT3A mut compared to AML NPM1 mut FLT3-ITD mut DNMT3A wt patients. Thus, GNG4 may play a role in the low survival rate of AML NPM1 mut FLT3-ITD mut DNMT3A mut patients, offering novel insights into the prognosis, therapeutic targets, and prognostic evaluation of AML.